(untitled) (Journal of the College of Education for Women, 2019)
The aims of this research is to investigate : The nature of academic specialization of the officials of Baghdad University Presidency , Level of job performance of the officials of Baghdad University Presidency through job performance appraisal form per year , Differences in the levels of job performance of the officials of Baghdad university presidency , according to the variables (sex , academic specialization , the current work , the duration between the date of graduation and the date of appointment , service duration) , The relationship of academic specialization of the officials of Baghdad university presidencywith their job performance . The researcher has followed the analytical descriptive mode to achieve the aims of this research . The population of the research includes the officials of Baghdad University Presidency having B . A degree in different specializations who are appointed as permanent cadre members , and those who have got job performance appraisal in (2009). This population consists of (290) officials ,Two resources have been used to achieve the aims : ( job information form ) and ( job performance appraisal form) . The present research results are : - That officials of Baghdad University Presidency have graduated from ( 21) different Colleges . They hold academic specializations (scientific , humanitarian). - That the job performance level is statistically evident when compared with the hypothetic medium (50) degree at the level (0,05) . - The presence of statistically evident differences in the levels of job performance on the sex , academic specialization , service duration, and no statistically evident differences in the current work, the duration between the date of graduation and the date of appointment . - There is no statistically evident relationship between the academic specialization and the job performance of Baghdad university presidency officials . According to the results and conclusions attained , the researcher has come to a number of recommendations and suggestions for research that will complement the subject of current research .